2015
DOI: 10.1007/s40615-015-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Persisting Racial Disparities in Total Shoulder Arthroplasty Utilization and Outcomes

Abstract: We found increasing racial disparities in TSA utilization. Some disparities in outcomes exist as well. Patients, surgeons, and policy-makes should be aware of these findings and take action to reduce racial disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…The authors also found higher risks of AKA following knee arthroplasty for patients who were younger than 50 and older than 80 years of age. The current findings regarding disparities in AKA usage are consistent with other orthopaedic procedures shown to be associated with racial or gender disparities [11], including lower extremity arthroplasty [2,12], total shoulder arthroplasty [13], cervical spine surgery [14], lumbar stenosis [8], and hip fractures [3].…”
supporting
confidence: 77%
“…The authors also found higher risks of AKA following knee arthroplasty for patients who were younger than 50 and older than 80 years of age. The current findings regarding disparities in AKA usage are consistent with other orthopaedic procedures shown to be associated with racial or gender disparities [11], including lower extremity arthroplasty [2,12], total shoulder arthroplasty [13], cervical spine surgery [14], lumbar stenosis [8], and hip fractures [3].…”
supporting
confidence: 77%
“…While healthcare utilization disparities have been shown in several areas of orthopedics, such as arthroplasty, upper extremity, and spinal surgeries, the literature has been limited within the field of orthopedic trauma [6, 8, 16]. Our study showed that several factors influence the treatment of closed calcaneus fractures in the US patient population.…”
Section: Discussionmentioning
confidence: 68%
“…Racial and social healthcare disparities have been identified within different elective areas of orthopedic surgery, such as hip and knee arthroplasty, shoulder arthroplasty, ankle arthroplasty, spinal fusion, cubital and carpal tunnel surgery, elective hardware removal following pediatric femoral shaft fractures, and treatment of meniscal tears [69, 13, 1622]. In particular, minorities were significantly less likely to undergo these elective orthopedic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Despite increasing utilization of total shoulder arthroplasty (TSA) as an effective management of various shoulder pathologies, [4][5][6] the literature has demonstrated that enduring racial and gender disparities exist in joint replacement procedures. [7][8][9][10][11][12][13][14][15] An 18-year analysis of Medicare part A data showed that in 1991, the use of primary total knee arthroplasty (TKA) was 36% lower for African-Americans compared with Caucasians. 1 Though utilization more than doubled for both African-Americans and Caucasians by 2008, the usage of primary TKA was still 40% lower for African-Americans.…”
Section: Introductionmentioning
confidence: 99%